EFEKTIVITAS KOPERATIF TERINTGRITAS MEMBACA DAN KOMPOSISI UNTUK KEMAHIRAN TERHADAP MENTAL DI SD NEGERI MOJOGEDANG - Adi Gunaryo, Sindu; Fathoni, Achmad (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
The number of bullying cases that exist in the world of education in Indonesia, so recently the minister of education and culture has issued a ministerial regulation on anti-bullying in new student orientation period activities through Permendikbud Number 55 of 2014 and circular letter Number 59389/MPK/PD/2015. The act of bullying occurs in several places in Karanganyar, namely in Mojogedang District, Mojogedang District, the purpose is to find out the role of parents in the importance of getting along in the Mojogedang State Elementary School environment and to find out the efforts made by parents in the importance of getting along in the Mojogedang State Elementary School environment. This research uses a theoretical basis including: 1) Reading Comprehension which is a process of obtaining meaning from the content of reading. Reading comprehension is required to be able to understand, interpret, analyze, and evaluate the content of reading; 2) Understanding the CIRC Learning Model as a systematic procedure; 3) Components in the CIRC Learning Model consisting of Team, Placement test, Student creative, and Team study. This research was conducted at Mojogedang State Elementary School, Mojogedang District, Karanganyar Regency, Central Java Province in the 2022/2023 academic year. This research uses a quantitative approach with a Pre-Experimental Design type of experiment. From this type of experiment, researchers used the One-Group Pretest-Posttest Deisgn design. In this study, the population used was class IV students of SD Negeri Mojogedang, totaling 8 students. Furthermore, in the methodology of sampling or what is also called sampling techniques. In this study using non-probability sampling technique, namely simple random sampling. The sample of this study was all fourth grade students consisting of 6 boys and 2 girls. The results showed that in the pretest, the minimum score was 40 and the maximum score was 70, with a mean of 57.50. In the posttest, the lowest score was 80 and the highest score was 90, with a mean of 86.25. This shows a significant difference between students' knowledge before and after using the CIRC method. The difference is due to the treatment or treatment of students' reading comprehension ability has increased after the application of the CIRC model.